Model Specification Tests and Artificial Regressions - MacKinnon, James G. (Journal of Economic Literature, 1992)
This work was supported, in part, by a grantfrom the Social Sciences and Humanities Research Council of Canada. The paper was written mostly while the author was on sabbatical at the University of California, San Diego. I am grateful to everyone there for providing such a hospitable environment, and to Anil Bera, Russell Davidson, David Hendry, Timo Teriisvirta, Pravin Trivedi, three referees, and seminar participants at the University of -Indiana for helpful comments on earlier versions.